New Higher Excited Energy Levels of Rydberg States for Weakest Bound Potential Model Theory: Extended Quantum Mechanics - AbdelmadjidВ Maireche (Журнал нано- та електронної фізики)
In present research paper, a BoppвЂ™s shift method and standard perturbation theory are used to find exact analytical solutions of the noncommutative 3-dimensional space phase (NC: 3D-RSP) for modified time-independent SchrГ¶dinger equation of weakest bound electron potential model (WBEPM) theory for neutral indium. We have obtained the explicit higher energy eigenvalues for excited states. Furthermore, the obtained corrections of energies are depended on the discreet atomic quantum numbers (,,and), in addition to the four infinitesimal parameters and which are induced by position-position and momentum-momentum noncommutativity, respectively. We have also shown that, the total complete degeneracy of higher energy level of the modified (WBEPM) theory equal the new values.